Cross-cultural adaptation of LIFE-H 3.1: an instrument for assessing social participation - Nunes de Assumpcao, Fernanda Sabine; Faria-Fortini, Iza de; Basilio, Marluce Lopes; Magalhaes, Livia de Castro; Carvalho, Augusto Cesinando de [UNESP]; Teixeira-Salmela, Luci Fuscaldi (Cadernos Saude Publica, 2016)
Restrictions in participation cause serious problems for individuals with chronic disabling conditions. The use of questionnaires to assess participation allows studying the impact of such chronic conditions on functionality, besides potentially improving intervention strategies. The aim of this study was to translate the Assessment of Life Habits (LIFE-H 3.1) into Brazilian Portuguese language and adapt the questionnaire to the Brazilian culture. The cross-cultural adaptation followed standard guidelines and was conducted in five stages: translation, back-translation, summary of the translations, expert committee consultation, and testing the pre-final version. The final version of the LIFE-H 3.1 for use in Brazil showed satisfactory semantic, linguistic, cultural, and conceptual equivalence. Future studies should continue the process of validating the questionnaire.
Keywords: Surveys and Questionnaires; Validation Studies; Social Participation